Development of a standardized histopathology scoring system for human intervertebral disc degeneration: an Orthopaedic Research Society Spine Section Initiative - Le Maitre, Christine L. (JOR Spine, 2021)
BACKGROUND: Histopathological analysis of intervertebral disc (IVD) tissues is a critical domain of back pain research. Identification, description, and classification of attributes that distinguish abnormal tissues form a basis for probing disease mechanisms and conceiving novel therapies. Unfortunately, lack of standardized methods and nomenclature can limit comparisons of results across studies and prevent organizing information into a clear representation of the hierarchical, spatial, and temporal patterns of IVD degeneration. Thus, the following Orthopaedic Research Society (ORS) Spine Section Initiative aimed to develop a standardized histopathology scoring scheme for human IVD degeneration. METHODS: Guided by a working group of experts, this prospective process entailed a series of stages that consisted of reviewing and assessing past grading schemes, surveying IVD researchers globally on current practice and recommendations for a new grading system, utilizing expert opinion a taxonomy of histological grading was developed, and validation performed. RESULTS: A standardized taxonomy was developed, which showed excellent intra‐rater reliability for scoring nucleus pulposus (NP), annulus fibrosus (AF), and cartilaginous end plate (CEP) regions (interclass correlation [ICC] > .89). The ability to reliably detect subtle changes varied by IVD region, being poorest in the NP (ICC: .89‐.95) where changes at the cellular level were important, vs the AF (ICC: .93‐.98), CEP (ICC: .97‐.98), and boney end plate (ICC: .96‐.99) where matrix and structural changes varied more dramatically with degeneration. CONCLUSIONS: The proposed grading system incorporates more comprehensive descriptions of degenerative features for all the IVD sub‐tissues than prior criteria. While there was excellent reliability, our results reinforce the need for improved training, particularly for novice raters. Future evaluation of the proposed system in real‐world settings (eg, at the microscope) will be needed to further refine criteria and more fully evaluate utility. This improved taxonomy could aid in the understanding of IVD degeneration phenotypes and their association with back pain.